Explaining the U-Shaped Development of Intent-Based Moral Judgments - Margoni, Francesco; Surian, Luca (Frontiers in Psychology, 2016)
When preschoolers evaluate actions and agents, they typically neglect agents’ intentions and focus on action outcomes instead. By contrast, intentions count much more than outcomes for older children and adults. This phenomenon has traditionally been seen as evidence of a developmental change in children’s concept of what is morally good and bad. However, a growing number of studies shows that infants are able to reason about agents’ intentions and take them into account in their spontaneous socio-moral evaluations. Here we argue that this puzzling U-shaped trajectory in children’s judgments is best accounted for by a model that posits developmental continuity in moral competence and emphasizes the effect of immature executive function skills on preschoolers’ performance.